Chaotic vibration of mechanical system with backlash - Ho, Kok Liang. (2010)
This Project is to investigate the existence of chaotic behavior in general mechanical system. The report begins with an introduction of background and follows by studying the classic dynamic systems and the properties of chaotic vibration. Several techniques are introduced and demonstrated to qualify as well as quantify the chaotic behavior. After revision of those techniques, a mechanical system is studied and finally a new mechanical system is investigated. The mechanical system with backlash and nonlinear was investigated and formulated into ordinary differential equation. The numerical simulation of the mechanical system was carried out and the chaotic behavior was found in Time-domain, Phase-space domain and Spectrum frequency. The Poincare map clearly showed the fractal structure of strange attractor and the quantitative techniques, Lyapunov exponent and Fractal dimension gave further indication of chaotic vibration. The results have shown that the chaotic vibration of mechanical system with backlash and nonlinear spring occurred in wide range of parameters. The chaotic vibration exhibited nonperiodic and unpredictable motion. It should be avoided during the design stage so that the mechanical system is able to be predicted in long time period.